Problematika Pernikahan Dini dalam Perspektif Hukum Keluarga Islam - Maulidya Nur Azmi; Nurul Nurul (Indo Publishing, 2026)
Even after Indonesia revised its Marriage Law to raise the minimum age to 19, early marriage remains a deeply rooted challenge within the country’s Islamic Family Law system. This study examines these ongoing issues through the dual lenses of contemporary Islamic Family Law and Maqashid Shariah. Utilizing a qualitative, normative-juridical method, the research analyzes relevant legal texts and scholarly perspectives. The findings reveal that modern Islamic Family Law has evolved to define maturity beyond biological markers, incorporating essential psychological and intellectual readiness. Under the framework of Maqashid Shariah, efforts to curb early marriage align directly with the core tenets of safeguarding life and preserving future generations. Ultimately, the study argues that tightening the loopholes for marriage dispensations in Religious Courts and boosting community legal literacy are vital steps toward building resilient families that yield genuine public benefits.